Fourth-order Q-enhanced band-pass filter tuning algorithm implementation and considerations - Schonberger, Joel Raymond (Kansas State University, 2010)
Q‐enhanced filtering technologies have been heavily researched, but have not yet been adopted into commercial designs due to tuning complexity, and performance issues such as noise figure and dynamic range. A multi‐pole Q‐enhanced band‐pass filter operating at 450 MHz with tunable bandwidth is developed in this thesis. A noise figure of 14 dB and dynamic range of 140 dB/Hz have been measured, making the filter suitable for operating in the IF subsystem of a radio receiver. The design utilizes off‐chip resonators, created using surface mount components or embedded passives in LTCC processes, to have a reasonably high base‐Q. The equivalent parallel loss resistance of the finite‐Q inductor and connected circuitry at resonance is partially offset by negative resistances, implemented with tunable on‐chip transconductors, as required to reach the needed Q for the targeted bandwidth. Each pole of the filter has binary weighted negative resistance cells for Q‐enhancement and binary weighted capacitances for frequency tuning. Binary weighted capacitive coupling cells allow the filter to achieve the level of coupling appropriate to the targeted bandwidth. To maintain the filter bandwidth, center frequency, and gain over environmental changes a realtime tuning algorithm is needed. A low complexity tuning algorithm has been implemented and found to accurately maintain the bandwidth, center frequency, and gain when operating at bandwidths of 10 or 20 MHz. Flatness of the pass‐band is also maintained, to within 0.5 dB across a temperature range of 25‐55 degrees C. In addition to the implementation of the tuning algorithm, the thesis provides a solution for pass‐band asymmetries spawned from the use of finite‐Q resonators and associated control circuitry.
Keywords: Q-enhanced; Intermediate frequency; Filter; Radio; Wireless; Tuning; Engineering, Electronics and Electrical (0544)